2017
DOI: 10.11118/actaun201765041241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Training Methods Applied to Apple Trees Trained to Slender Spindle During the First Years After Planting

Abstract: The research was focused on the comparison of two pruning methods (winter pruning and winter + summer pruning) applied to apple trees trained to a standard and a modified slender spindle. The orchard of 'Topaz' trees, grafted on rootstock M 9, was planted in spring 2011. In the years 2013 -2016, trunk cross sectional area (TCSA), crown volume, cumulative yields, yield efficiency, relative proportion of fruit size classes, number of cuts and dry matter of pruned wood were analyzed. The total growth intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similar results were obtained by Melnik and Kravtsova (2019) with the 'Gala' and 'Jonagold' cultivars. Mészáros et al (2017) reported increased specific productivity per stem cross-sectional area and total shoot length as a result of summer pruning.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Melnik and Kravtsova (2019) with the 'Gala' and 'Jonagold' cultivars. Mészáros et al (2017) reported increased specific productivity per stem cross-sectional area and total shoot length as a result of summer pruning.…”
Section: Resultsmentioning
confidence: 99%
“…In apple cv. Topaz grafted on M9 rootstock, trees trained as modified slender spindle had lower canopy volume compared to slender spindle and demonstrated better tree size control (Mészáros et al, 2017). Trees of cherry cv.…”
Section: Pruning and Trainingmentioning
confidence: 99%
“…Information perception studies have shown that the crown determines the growth and development of trees, which in turn affects their yield and economic benefits [2]. Canopy characteristics have important guiding significance for research related to trees, because they can usually be used for growth assessment [3], biomass estimation [4,5], pruning effect analysis [6], yield prediction [7], health assessment early disease detection [8,9] and in the use of plant protection products such as insecticides [10]. Fruit tree canopy characteristics include canopy height, width, and volume.…”
Section: Introductionmentioning
confidence: 99%